2020
DOI: 10.21203/rs.3.rs-39061/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

K284-6111 Alleviates Memory Impairment and Neuroinflammation in Tg2576 Mice by Inhibition of Chitinase-3-like 1 Regulating ERK Dependent PTX3 Pathway

Abstract: Background Alzheimer's disease (AD) is one of the most prevalent neurodegenerative disorders characterized by gradual memory loss and neuropsychiatric symptoms. We have previously demonstrated that the 2-({3-[2-(1-Cyclohexen-1-yl)ethyl]-6,7-dimethoxy-4-oxo-3,4-dihydro-2-quinazolinyl}sulfanyl)-N-(4-ethylphenyl)butanamide (K284-6111), the inhibitor of CHI3L1, has an inhibitory effect on memory impairment in Αβ infusion mouse model and on LPS-induced neuroinflammation in the murine BV-2 microglia and primary cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…The CHI3L1 inhibitor reduced the number of iNOS, COX-2, GFAP, and Iba-1 positive cells, indicating an inhibition of microglial and astrocytic activation, and also decreased the levels of TNF-α, IL-1β, and IL-6 in the brains of the Tg2576 transgenic mice. 92 These results are consistent with the group's previous results in the Aβ 1-42 -induced AD model.…”
Section: Known Effects Of Chi3l1 On Neuroinflammation and Adsupporting
confidence: 93%
See 2 more Smart Citations
“…The CHI3L1 inhibitor reduced the number of iNOS, COX-2, GFAP, and Iba-1 positive cells, indicating an inhibition of microglial and astrocytic activation, and also decreased the levels of TNF-α, IL-1β, and IL-6 in the brains of the Tg2576 transgenic mice. 92 These results are consistent with the group's previous results in the Aβ 1-42 -induced AD model.…”
Section: Known Effects Of Chi3l1 On Neuroinflammation and Adsupporting
confidence: 93%
“…91 Furthermore, in the brain, the same CHI3L1 inhibitor decreased the M1 markers TNF, IL-1β, IL-6, and CD86, while CHI3L1 overexpression increased the expression of these M1 markers. 92 Conversely, M2 markers such as Arg1, Mrc1, TGF-β, and IL-10 were unaffected by the inhibition of CHI3L1. 92 This indicates that CHI3L1 may drive the activation of microglia to an M1, pro-inflammatory phenotype.…”
Section: Chi3l1's Effect On Cns Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…6). Most importantly, increased Ptx3 secretion may correlate with neurodegenerative disease progression, such as Alzheimer's disease and Parkinson's disease 7,24,25 . Thus, Ptx3 may act as therapeutic target for neurodegenerative disease and spinal cord injury, and support the ongoing development of synthetic peptide RI37 for the treatment of spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…Pentraxin-3 (Ptx3) belongs to the long pentraxin family and is expressed in a variety of cell type, especially astrocyte in central nervous system 7,8 . Previous study showed that astrocytic Cebpd can activate Ptx3 expression that inhibit macrophage-mediated phagocytosis 9 .…”
Section: Introductionmentioning
confidence: 99%